Robust and Area Efficient 4H-SiC 1.2 and 3.3 kV Floating Field Ring (FFR) and Trench-FFR Termination Designs and Analysis - Melnyk, Kyrylo; Gammon, Peter Michael; Renz, Arne Benjamin; Cao, Quize; Lophitis, Neophytos; Antoniou, Marina (My University, 2023)
A robust and efficient termination is a crucial component of a high-power device, requiring careful design and calibration. Multiple techniques were demonstrated across the literature, such as FFRs, Junction Termination Extensions (JTEs), Trench-FFR (T-FFR) etc. Widely used FFR and JTE terminations have their limitations, such as large area consumption and doping dose sensitivity. Moreover, during prolonged stresses, the positive charge can occur at the oxide passivation interface, resulting in Electric Field (EF) perturbation and reduced Breakdown Voltage (BV). This paper presents the comparison between FFR and T-FFR structures for both 1.2 kV and 3.3 kV blocking, with the analysis and optimization for the positive charge accumulation. Without the influence of the positive charge, 1.2 kV/3.3 kV T-FFR reduces the area consumption by 28 % compared to FFR. Optimized T-FFR for charge immunity, designed for 1.2kV reduces area consumption by 20.5 % and for 3.3kV by 27 %, while outperforming 3.3kV FFR in blocking efficiency with charge densities higher than 6x1012 cm-2 at the oxide interface.
Keywords: United Kingdom